The correlation between ferritin level and cardiac dysfunction in patients with thalassemia - Fajar Subroto; Bulan Ginting Munthe; Najib Advani; Agus Firmansyah (Paediatrica Indonesiana, 2003)
Background Patients with b-thalassemia major, long-term trans-fusion, extravasal hemolytic, and increased intestinal absorptionof iron result in systemic iron overload, which may accumulate inmyocardium causing cardiac dysfunctions. Congestive heart fail-ure usually develops in adolescence or early adult years, and pa-tient usually dies within 1 year after the onset of symptoms. There-fore, it is important to detect early signs of cardiac dysfunction inpatient with thalassemia.Objective This study aimed to assess the correlation betweenferritin level and cardiac dysfunction in patients with thalassemia.Methods A cross sectional study was conducted on 62 b-thalas-semic patients (34 males and 28 females) with age ranging from3.5 to 23 years. They received 3,150 – 94,985 mL of blood; withthe serum ferritin level of 812.2 – 12,175 ng/mL. Each patient un-derwent laboratory examinations and clinical cardiac evaluationwith ECG and echocardiography.Results Cumulative blood transfusions correlated well with theserum ferritin values (p=0.001). The serum ferritin level did notshow correlation with deferoxamine (DFO) treatment. ECG exami-nation revealed 5 patients (8.1%) with dysrhythmia, LVH, and heartblock grade II and I. Echocardiography examination showed 18patients (29%) with systolic or diastolic dysfunction. There was nocorrelation between the serum ferritin level and cardiac dysfunc-tions (p=0.640). The serum ferritin prediction value against car-diac dysfunctions could not be established.Conclusion There was no correlation between serum ferritin lev-els with cardiac dysfunctions. In detecting cardiac dysfunctions inthalassemic patients, echocardiography was more sensitive thanECG